The Quality Lecture: How Do We Rate? (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
Aims: to review the key features of an effective lecture and to rate a series of medical school lectures to inform a broader initiative in staff development in effective lecturingBackground: Lectures are the primary method of delivering information to an audience in tertiary education and remain a key part of medical school educationMethod: Literature review confirmed fourteen elements thought to contribute to the quality of a lecture. A lecture series was then rated using these criteriaResults: The three highest rated criteria were explaining and summarising key concepts, presenting material at an appropriate level to the audience, and the use of clear audio-visual aids and voice. The three lowest rated aspects of our lecture program were stating goals of the talk, monitoring audience understanding and responding appropriately, and providing a conclusion to the talk.Conclusions: These findings will provide direction to staff development to further improve the quality of lectures provided to students.